Pengaruh Kualitas Pelayanan Customer Service Dan Kepuasan Nasabah Terhadap Loyalitas Nasabah Pada Bank Syariah Indonesia Kantor Kas IAIN Sulthan Thaha Saifuddin Kota Jambi - Khusnul Istiqomah; Ahsan Putra Hafiz; Abdul Hakim Saputra (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
In the current era of globalization, the rapid growth and development of sharia banking in Indonesia has given rise to competition between sharia financial institutions which is getting tighter from year to year, therefore both state and private banks are launching various strategies to attract potential customers or existing customers. Are interested so that they remain loyal customers. Service quality and customer satisfaction are one of several factors that influence customer loyalty. Service quality is expected to provide encouragement to customers to maintain a strong relationship with the bank. Customer satisfaction shapes customer perceptions and can then position the product in their minds. The aim of this research is to determine the influence of customer service quality and customer satisfaction on customer loyalty at Bank Syariah Indonesia, IAIN Sulthan Thaha Saifuddin Caash Office, Jambi City. The Number ofsamples in this research was 100 people and used a non-probability sampling technique, namely incidental sampling. Multiple Regression Analysis is used as a data analysis technique. The research result show that service quality and customer satisfaction have a positive and significant effect on customer loyalty. Based on data analysis in this research, these variables are valis and reliable. When testing classical assumptions with a normal distribution, heteroscedasticity and multicollinearity do not occour.